Lucius Brutus of Rome and Cypselus of Corinth - Rung, Ádám (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
The story of Lucius Brutus, the founder of the Roman Republic has often been analysed as a historical story, somewhat mythicised, and embellished by literary tropes; and some have also interpreted it as primarily a myth, historicised by a later Roman culture more interested in the exemplary than in the marvelous. Starting out in the latter tradition, this article explores a connection that has been hinted at from antiquity, and has been analysed from the historical and historiographic perspective to some extent, but has not been interpreted in detail as a connection between two myths: the numerous parallels that the story of Brutus and the Tarquins, as told by Virgil, Livy and Ovid, has to the saga of the aristocratic Bacchiad and the tyrannical Cypselid families of early Corinth, as told by Herodotus and Aristotle. The newly discovered parallels (and the re-examination of the known ones) between these stories also invite the reader to reflect on the ways they might have evolved, their political and cultural functionality and on the complex interplay between myth and history.